PENGARUH CAPITAL INTENSITY, FAMILY OWNERSHIP DAN STRATEGI BISNIS TERHADAP TAX AVOIDANCE - Wulandari; Fikriyah, Siti Hailatul (Jurnal Nusa Akuntansi, 2024)
This research aims to find out and provide empirical evidence regarding Capital Intensity, Family Ownership and Business Strategy towards Tax Avoidance in Non-Cylinical Consumer Companies listed on the Indonesia Stock Exchange for the period 2018-2023. The type of research used is quantitative research. The number of samples in this study was 30 observation data from 5 non-cyclical consumer companies for the 2018-2023 period which was obtained using a purposive sampling method based on the criteria that had been carried out. The data used is secondary data, namely in the form of annual financial reports for the 2018-2023 period obtained from the official website of the Indonesian Stock Exchange and the official websites of each company. The data analysis technique used is data regression analysis using e-views 12 software. The results of this research based on partial test results state that Capital Intensity has an effect on Tax Avoidance, while Family Ownership and Business Strategy have no effect on Tax Avoidance. Based on the simultaneous test, it states that Capital Intensity, Family Ownership and Business Strategy simultaneously influence Tax Avoidance.